2021
DOI: 10.3390/molecules26040816
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cytotoxic Activity of Selected Isoquinoline Alkaloids and Plant Extracts Obtained from Various Parts of Mahonia aquifolium Collected in Various Vegetation Seasons

Abstract: Melanoma is a serious form of skin cancer that begins in cells known as melanocytes. While it is less common than the other forms of skin cancer, melanoma is more dangerous because of its ability to spread to other organs more rapidly if it is not treated at an early stage. The number of people diagnosed with melanoma has increased over the last few decades. The most widely used treatments include surgery, chemotherapy, and radiation therapy. The search for new drugs to treat various cancers is one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The rhizomes of Coptis chinensis are rich sources of different types of isoquinoline alkaloids, that had been proved to inhibit the development of cancer cells in various in vitro and in vivo models of different types of cancer [ 43 , 44 , 45 , 46 , 47 ]. However, to perform the experimental studies, pure compounds are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The rhizomes of Coptis chinensis are rich sources of different types of isoquinoline alkaloids, that had been proved to inhibit the development of cancer cells in various in vitro and in vivo models of different types of cancer [ 43 , 44 , 45 , 46 , 47 ]. However, to perform the experimental studies, pure compounds are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Sanguinaria canadensis extracts exhibited highly cytotoxic activity compared to previously published investigations of various plant extracts cytotoxicity against different melanoma cells [26][27][28][29][30][31][32][33][34][35][36]. IC 50 values obtained after exposure of A375 cells to Sanguinaria canadensis extracts were from 4.09 to 10.96 µg/mL, values after exposure of G-361 cells to the plant extract were from 1.22 to 1.60 µg/mL, and after exposure of SK-MEL-3 to the same extracts were from 0.88 to 1.36 µg/mL.…”
Section: Comparison Of In Vitro Cytotoxic Activity Of Sanguinaria Canadensis Extracts With Cytotoxic Activity Of Various Plant Extractsmentioning
confidence: 94%
“…Our results demonstrated that Sanguinaria canadensis extracts are cytotoxic to various human melanoma cell lines, with IC 50 values ranging from 0.88 to 10.96 µg/mL. Interestingly, the cytotoxicity was greater than that of other plant extracts containing various cytotoxic compounds, including alkaloids [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Investigation Of In Vitro Cytotoxic Activity Of Sanguinaria Canadensis Extractsmentioning
confidence: 98%
“…The isoquinoline alkaloid standards berberine, chelerythrine, magnoflorine, palmatine, protopine and sanguinarinee (Table 1) were chromatographed on a Polar RP column with mobile phase containing acetonitrile, water and 0.04 ML −1 of 1-butyl-3 methylimidazolium tetrafluoroborate in a gradient elution system as described in the Experimental Section. The chromatographic conditions were based on a previously published procedure after appropriate modification [42]. The π-π interaction retention times (t R ), asymmetry factors (As), and theoretical plate number per meter (N/m) obtained for the investigated alkaloid standards with the chromatographic system containing addition of ionic liquid in the mobile phase and phenyl stationary phase are presented in Table 1.…”
Section: Hplc-dad Analysis Of Alkaloid Standards and Plant Extractsmentioning
confidence: 99%